2020
DOI: 10.1038/s41467-020-15418-2
|View full text |Cite
|
Sign up to set email alerts
|

A bifunctional asparaginyl endopeptidase efficiently catalyzes both cleavage and cyclization of cyclic trypsin inhibitors

Abstract: Asparaginyl endopeptidases (AEPs) catalyze the key backbone cyclization step during the biosynthesis of plant-derived cyclic peptides. Here, we report the identification of two AEPs from Momordica cochinchinensis and biochemically characterize MCoAEP2 that catalyzes the maturation of trypsin inhibitor cyclotides. Recombinantly produced MCoAEP2 catalyzes the backbone cyclization of a linear cyclotide precursor (MCoTI-II-NAL) with a k cat /K m of 620 mM −1 s −1 , making it one of the fastest cyclases reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(134 citation statements)
references
References 65 publications
3
117
0
2
Order By: Relevance
“…3). As demonstrated here and in previous works, 27,37 AEP functions from pH $5.0-7.5, but some proteins may become unstable even under mildly acidic environments. Hence, the presented labeling system was also tested with the engineered lumazine synthase AaLS-13, a macromolecular complex composed of 360 protein subunits which is prone to precipitation at pH below 7.0.…”
Section: Oaaep1-c247a Mediated Protein Bioconjugationsupporting
confidence: 78%
See 1 more Smart Citation
“…3). As demonstrated here and in previous works, 27,37 AEP functions from pH $5.0-7.5, but some proteins may become unstable even under mildly acidic environments. Hence, the presented labeling system was also tested with the engineered lumazine synthase AaLS-13, a macromolecular complex composed of 360 protein subunits which is prone to precipitation at pH below 7.0.…”
Section: Oaaep1-c247a Mediated Protein Bioconjugationsupporting
confidence: 78%
“…Protein-based approaches offer the ability to function efficiently under mild reaction conditions. 5,6 Transferase, [13][14][15] oxidoreductase, [16][17][18] ligase, 19,20 transpeptidase 2,4,[21][22][23][24][25][26][27] and (split-)intein [28][29][30] have been applied for protein bioconjugation. Nevertheless, adapting these enzymes or proteins for synthetic applications, which deviate from their natural function, oen results in technical issues.…”
Section: Introductionmentioning
confidence: 99%
“…The structural features that make AEP favour hydrolysis or transpeptidation remains a matter of debate. Recent work by Du et al (2020) uncovered a plant AEP with one of the highest transpeptidase activities despite predictions, based on previously published AEPs, that it would be a hydrolase. Here we compared CeAEP1 structure to butelase1, an extremely efficient transpeptidase with efficiency up to 1,340,000 M -1 s -1 , and to VyPAL2, OaAEP1, AtLegγ, and HaAEP1, which have intermediate to low transpeptidase efficiency.…”
Section: Ceaep1 Is Predominantly a Proteasementioning
confidence: 99%
“…31 A disadvantage of sortase and trypsiligase is their strict recognition sequence requirements, whereas subtiligase requires a C-terminal carboxamidomethyl ester on the CP. AEPs are highly efficient at catalyzing backbone cyclization of linear peptides, 32,33 rendering them attractive tools for chemoenzymatic cyclization. AEPs require a simple tripeptide Asx-Xaa-Yaa (P1-P1ʹ-P2ʹ) recognition motif, where Asx is Asn or Asp in position P1 followed by any small residue in P1ʹ and a hydrophobic or aliphatic amino acid in P2ʹ.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to overcome this limitation is intein-mediated backbone cyclization but the requirement for a reduced cysteine at the cyclization/processing sites may be problematic for certain peptides. 37,39,40 AEPs are ideally suited for cyclization applications because they are highly efficient at catalyzing backbone cyclization of naturally occurring cyclic peptides 32,33 and require minimal recognition sequences. 34 Poon et al demonstrated that cyclic peptides can be produced in plant-based expression systems by co-expressing an asparaginyl endopeptidase (AEP) with a peptide precursor equipped with a suitable cyclization motif.…”
Section: Introductionmentioning
confidence: 99%